Nanodelivery of Cerebrolysin as adjunct therapy with Functionalized magnetic iron oxide nanoparticles enhances neuroprotection following whole body hyperthermia - Sharma A.; Muresanu D.F.; Lafuente J.V.; Menon P.; Patnaik R.; Tian Z.R.; Mos̈sler H.; Sharma H.S. (My University, 2025)
The incidences of breast and lung cancer in military personnel are very high. Recently, functionalized magnetic iron oxide nanoparticles (FMIONPs) are used as safe adjuvant therapy in cancer patients with chemotherapy or heat treatment to destroy cancerous cells effectively. However, we found that FMIONPs following whole body hyperthermia (WBH) like cancer therapy resulted in exacerbation of brain pathology within 24 h. Thus, in this innovation we used Cerebrolysin (a balanced composition of neurotrophic factors and active peptide fragments) with or without TiO2 nanowired together with FMIONPs administration to reduce brain damage following WBH in the rat. The nanowired Cerebrolsyin significantly reduced brain pathology caused by FMIONPs following WBH. This innovation suggests that nanowired delivery of Cerebrolsyin, as an adjunct therapy is needed in cancer patients where FMIONPs are required to enhance the effects of chemotherapy or heat treatment.